Cytopathology of Extragenital Transmissible Venereal Tumour in a Dog - Jadhao, Abhilash; Baba, Omer K.; Gupta, Kuldip (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Transmissible Venereal Tumour (TVT) is a horizontally transmitted tumor of dogs, also known as canine  transmissible venereal sarcoma, venereal granuloma,  transmissible lymphosarcoma, or sticker tumor of mesenchymal  origin (Saravanan et al., 2015). TVT can easily transmit from  animal to animal during copulation by viable tumor cells  by licking, biting, and by direct contact with the tumor and  frequently affects dogs of either sex (Sritrakoon et al., 2020).  TVT occasionally affects internal genitalia and extragenital  sites such as skin, mouth, eye, nasal and other sites too (Gupta  and Sood, 2012; Saravanan et al., 2015; Sritrakoon et al., 2020  and Dhillon et al., 2021). TVT is distinguished morphologically  into three cytomorphological types: (1) Lymphocytic type,  having granular cytoplasm with centrally placed nucleus  and intracytoplasmic vacuoles. (2) Plasmocytic type, having  eccentric nuclei with many cytoplasmic vacuoles, and (3) Mixed  type, characterized by both lymphocytic and plasmacytic types  (Florez et al., 2016). The histological features of TVT resemble  histiocytoma, whereas in the cytology of TVT, cytoplasm  reveals punctuate vacuoles in most cells that differ from  histiocytic tumor and other round tumor cells (Abeka, 2019).  The present case report deals with the hematobiochemical,  cytological, and histopathological findings in an unusual case  of extragenital TVT in a dog.
Keywords: Transmissible Venereal Tumour; (TVT); venereal granuloma; tumor of dogs